Genetic Relationship among Paphiopedilum Subgenus Brachypetalum Section Brachypetalum Using HAT-RAPD Markers - Meesangiem, Teepaka; Damrianant, Somchit; Thanananta, Theerachai; Thanananta, Narumol (Thai Journal of Science and Technology, 2017)
Abstract Genetic relationship of lady’s slipper orchids, Paphiopedilum subgenus Brachypetalum section Brachypetalum, 14 varieties found in Thailand, was demonstrated by HAT-RAPD markers. The total of 72 random primers were screened and 29 primers could be used for DNA amplification. Twenty-two primers were selected and used to analyze each DNA species of all samples. A dendrogram was constructed, based on polymorphic bands, and showed genetic similarities among 4 clusters with the similarity coefficients ranging from 0.32 to 0.81 as well as the analysis of genetic diversity. Keywords: Paphiopedilum; genetic relationship; HAT-RAPD marker